Lesson study in initial teacher education : principles and practices - Wood, Phil; Lynn Sorton Larssen, Deborah; Cajkler, Wasyl; Helgevold, Nina (Bingley, U.K. : Emerald Publishing Limited, 2019)
This book explores the use of lesson study within the context of initial teacher education. The lesson study process is broken down into its main components and these elements are discussed with references to the specific needs of practitioners, educators and researchers in initiating and developing lesson study in teacher education.Lesson Study in Initial Teacher Education highlights the importance of embedding lesson study within initial teacher education programmes, including building partnerships, making time to carry out collaborative inquiries using lesson study, and frameworks for reporting on lesson study projects. Written by a group of researcher practitioners with extensive experience in developing and managing lesson study in initial teacher education programmes, this book presents a critical overview of the principles and practices at the core of developing collaborative inquiry amongst those being educated to become teachers. By outlining an innovative framework to support professional learning classroom-based research, this book will prove invaluable for researchers, administrators and leaders in teacher education.
Chapter 1. International changes and approaches in initial teacher education / Nina Helgevold and Chris Wilkins -- Chapter 2. An introduction to lesson study / Deborah L S Larssen -- Chapter 3. Lesson study in ITE - a family of approaches / Wasyl Cajkler and Phil Wood -- Chapter 4. Whose learning in ITE lesson study? Gaining the most from lesson study in relation to learning / Hans Erik Bugge -- Chapter 5. The role of collaborative planning - how to use joint planning as a learning process in lesson study / Julie Norton, Nina Helgevold and Raymond Bjuland -- Chapter 6. The role of observation in ITE lesson study / Phil Wood, Wasyl Cajkler and Arne Jakobsen -- Chapter 7. Capturing other perspectives - lesson artefacts, pupil voice, and participatory potential in ITE lesson study / Rebecca Charboneau Stuvland -- Chapter 8. Reflective practice and the lesson study process in initial teacher education / Gro Næsheim- Bjørkvik and Deborah Lynn Sorton Larssen -- Chapter 9. Student-teachers' written reports about their own learning processes from lesson study / M. Neus Álvarez, M.Laura Angelini, Inmaculada López-Lull and Chiara Tasso -- Chapter 10. Tools for helping student-teachers learning the complex work of teaching in lesson study cycles / Janne Fauskanger and Raymond Bjuland -- Chapter 11. Lesson study partnerships in initial teacher education / Fay Baldry and Colin Foster -- Chapter 12. The thorny issue of time / Phil Wood -- Chapter 13. Normalization process theory in ITE lesson study / Phil Wood and Wasyl Cajkler -- Chapter 14. The wider perspective on lesson study - developing a holistic view of practitioner development through pedagogic literacy / Wasyl Cajkler and Phil Wood -- Chapter 15: The future of lesson study in initial teacher education -- Index.
Includes index.
Print version record.
Keywords: Lesson planning -- Study and teaching; Teachers -- Training of; Education -- Teaching Methods & Materials -- General; Curriculum planning & development